Fiber-reinforced reactive magnesia-based tensile strain-hardening composites - Ruan, Shaoqin (2019)
This study focuses on the development of a new strain-hardening composite (SHC) involving carbonated reactive MgO cement (RMC) and fly ash (FA) as the main binder. Rheological properties of the developed composites were investigated by varying FA and water contents to achieve desirable fiber dispersion. A suitable mix design, in which polyvinyl alcohol (PVA) fibers were introduced to provide tensile ductility, was determined. The effect of key parameters such as w/b ratio and curing age on the mechanical properties of carbonated RMC-SHC was evaluated. Adequate binder content and w/b ratio was necessary for desirable fiber dispersion. Lower water contents and longer curing ages contributed to the strength development of RMC-SHC by improving the fiber-matrix interface bond and enhancing the formation of a dense carbonate network.